FORMULATION AND EVALUATION OF SACHA INCHI OIL LIP BALM PREPARATIONS WITH CONCENTRATION VARIATIONS OF CERA ALBA AND LANOLIN AS LIP BALM - Putri, Chintiana Nindya; Latifah, Fadzil; Zahro, Honest Fatimatuz (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Lip balm is used on lips that require protection, such as when humidity is low, to prevent the evaporation of water and epithelial cells on the lip mucosa. The active substance used in making this lip balm is Sancha inchi oil, which is a cold-pressed oil from the seeds of Plukenetia volubilista. This oil contains omega 3 (40–50%) and omega 6 (30–40%), as well as lower oleic acid (10%) than olive oil. Natural antioxidants, including tocopherols and polyphenols, have also been found in Sacha Inchi oil. Sacha inchi oil has a fatty acid ratio and phytochemical composition, it can be used as a cosmetic ingredient as an emollient and skin protector. An experimental laboratory method was used for this study. The research was carried out by preparing lip balm from various ingredients containing the active ingredient Sacha inchi oil (Plukenetia volubilis L) at a concentration of 15%, as well as varying concentrations of cera alba (range 5-25%) and lanolin (range 2-10%) as bases and additional ingredients for preparations, whose optimization had been determined using the simplex lattice design method. The aim of this study was to identify the lip balm formulation from Sacha inchi oil and identify the effect of changes in the concentration of cera alba and lanolin based on the results of the preparation evaluation. The results of this test show that sacha inchi oil can be used as an active lip-moisturizing agent in lip balm preparations ...